Perinatal and Early-Life Determinants of Infantile Colic and Non-Colic Excessive Crying - Siraj Nabi, Javid Iqbal, Farheen Naseem, Saba Wamiq, Mohammad Shahid Iqbal (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Excessive crying during infancy, including infantile colic and non-colic excessive crying, is a common concern among caregivers and a frequent cause of pediatric consultations. Objectives: To investigate the perinatal and early-life risk factors associated with infantile colic and non-colic excessive crying in term infants during the first three months of life. Methods: This prospective observational cohort study was conducted at ibn-e- siena hospital and research Institue Multan during January 2022 to November 2022. A total of 380 infants and their primary caregivers were enrolled in the study. Infants born at term (gestational age ≥ 37 weeks), singleton births, and the absence of major congenital anomalies or chronic illnesses were included in the study. Participants comprised of premature birth, significant perinatal asphyxia, known genetic syndromes, and parents with major psychiatric disorders that could impede reliable reporting were excluded. Results: Infantile colic was observed in 17.6% of infants and non-colic excessive crying in 22.4%, with a combined prevalence of 40%. Cesarean delivery (AOR = 2.14; 95% CI: 1.23–3.71), formula feeding (AOR = 2.89; 95% CI: 1.65–5.06), high maternal prenatal stress (AOR = 1.78; 95% CI: 1.01–3.12), and passive smoking (AOR = 1.94; 95% CI: 1.05–3.59) were significant predictors of infantile colic. Non-colic excessive crying was independently associated with maternal postnatal depression (AOR = 2.37; 95% CI: 1.31–4.31), low maternal-infant bonding (AOR = 1.88; 95% CI: 1.06–3.31), and lower household income (AOR = 1.65; 95% CI: 1.01–2.69). Conclusion: It is concluded that both infantile colic and non-colic excessive crying are influenced by distinct but overlapping perinatal and psychosocial factors. While infantile colic is more strongly associated with biological and environmental exposures, non-colic crying is linked to caregiver mental health and socioeconomic stress. Keywords: Perinatal, Early life risk factor, colic, non colic, excessive crying